Loss of the cystine/glutamate antiporter in melanoma abrogates tumor metastasis and markedly increases survival rates of mice. Issue 11 (26th August 2020) - Sato, Mami; Onuma, Kunishige; Domon, Mio; Hasegawa, Shun; Suzuki, Ami; Kusumi, Ryosuke; Hino, Remi; Kakihara, Nahoko; Kanda, Yusuke; Osaki, Mitsuhiko; Hamada, Junichi; Bannai, Shiro; et al.
Abstract: The cystine/glutamate antiporter, system xc −, is essential for the efficient uptake of cystine into cells. Interest in the mechanisms of system xc − function soared with the recognition that system xc − presents the most upstream node of ferroptosis, a recently described form of regulated necrosis relevant for degenerative diseases and cancer. Since targeting system xc − hold the great potential to efficiently combat tumor growth and metastasis of certain tumors, we disrupted the substrate‐specific subunit of system xc −, xCT (SLC7A11) in the highly metastatic mouse B16F10 melanoma cell line and assessed the impact on tumor growth and metastasis. Subcutaneous injection of tumor cells into the syngeneic B16F10 mouse melanoma model uncovered a marked decrease in the tumor‐forming ability and growth of KO cells compared to control cell lines. Strikingly, the metastatic potential of KO cells was markedly reduced as shown in several in vivo models of experimental and spontaneous metastasis. Accordingly, survival rates of KO tumor‐bearing mice were significantly prolonged in contrast to those transplanted with control cells. Analyzing the in vitro ability of KO and control B16F10 cells in terms of endothelial cell adhesion and spheroid formation revealed that xCT expression indeed plays an important role during metastasis. Hence, system xc − emerges to be essential for tumor metastasis in mice, thus qualifying as a highly attractive anticancer drug target, particularly in light of its dispensable role for normal life in mice. Abstract : What's new? The cystine/glutamate antiporter system xc‐ has generated growing interest as the most upstream node of ferroptosis, a recently‐described iron‐dependent form of necrotic cell death that is highly relevant in cancer. Using mouse cell‐based assays and in vivo murine cancer models, here the authors demonstrate that system xc‐deficiency not only impairs primary tumor growth but also abrogates tumor dissemination and metastasis in melanoma. The results also show in tumor‐bearing mice that reduced metastasis coincides with increased overall survival. Overall, the findings support the essential role of system xc‐ in tumor metastasis and its potential as an attractive anti‐cancer drug target.